Polycystic ovarian syndrome in identical twins. Issue 699 (January 1984) - Hutton, C.; Clark, F.
Abstract : Two 21-year-old female twins are described. They presented simultaneously with hirsutism and oligomenorrhoea. Investigation showed they had polycystic ovaries, they were identical and were not cases of post-pubertal adrenogenital syndrome.